2023
DOI: 10.1182/blood.2022017686
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab plus decitabine for patients with MDS or AML in posttransplant or transplant-naïve settings

Abstract: Two articles in this week’s issue focus on the use of ipilimumab and decitabine for patients with myelodysplasia (MDS) and acute myeloid leukemia (AML) before and after hematopoietic stem cell transplantation (HSCT) for high-risk disease. In the first article, Garcia et al report on the results of a phase 1 trial of the combination in 54 patients, demonstrating overall response rate of 52% in patients who are HSCT-naïve and 20% in patients post-HSCT; responses are usually short-lived. In the second article, Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…27 Decitabine combined with ipilimumab resulted in a CR/CRi in 5/25 (20%) patients with post-allo-HCT relapse. 53 Our data align with the literature and demonstrate that long-lasting responses to PD-1 blockade, even in combination with HMA and DLI, are seen primarily in individual patients. We propose that HMA/ nivolumab can be applied as a "bridging" approach to the subsequent treatment, such as a second allo-HCT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…27 Decitabine combined with ipilimumab resulted in a CR/CRi in 5/25 (20%) patients with post-allo-HCT relapse. 53 Our data align with the literature and demonstrate that long-lasting responses to PD-1 blockade, even in combination with HMA and DLI, are seen primarily in individual patients. We propose that HMA/ nivolumab can be applied as a "bridging" approach to the subsequent treatment, such as a second allo-HCT.…”
Section: Discussionsupporting
confidence: 90%
“…In comparison, CTLA‐4 blockade with ipilimumab induced a CR in 5/12 (42%) patients with myelodysplastic syndrome/AML 27 . Decitabine combined with ipilimumab resulted in a CR/CRi in 5/25 (20%) patients with post‐allo‐HCT relapse 53 . Our data align with the literature and demonstrate that long‐lasting responses to PD‐1 blockade, even in combination with HMA and DLI, are seen primarily in individual patients.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, response rates (defined as CR/CRi at any timepoint during the study) were 20% (5 of 25, arm A) vs 52% (12 of 23, arm B). 10 Longitudinal sampling of peripheral blood and bone marrow was obtained at study entry ('Screening'), following decitabine priming (end of lead-in, ~day 30), after introduction of ipilimumab (Cycle 1, ~day 60) and at pre-defined later timepoints including at the end of treatment ('EOT', day 48 -531).…”
Section: Baseline Features Predictive Of Response To Decitabine/ipili...mentioning
confidence: 99%
“…Based on this concept, we recently reported the clinical results of the phase I ETCTN/CTEP 10026 study, which tested combined decitabine with ipilimumab both in relapsed AML following HSCT (Arm A) and in transplant-naïve AML/MDS (Arm B). 9,10 Arm A was motivated by clinical responses in extramedullary AML post-HSCT treated with ipilimumab monotherapy (ETCTN/CTEP 9204). 5,11 The objective response rates of ETCTN/CTEP 10026 revealed 5 of 25 (Arm A) and 12 of 23 (Arm B) patients achieving CR/CRi.…”
Section: Introductionmentioning
confidence: 99%
“…First, there appear to be a sizeable minority of patients who will experience excess toxicity during therapy, such as the development of pneumonitis, and there is a signal for early mortality with atezolizumab and azacitidine [39]. Several studies explored combinations of pembrolizumab, nivolumab, or ipilimumab with DNTMI, although again it was not clear that there was advantage over azacitidine monotherapy [35,[40][41][42][43]. Indeed, a randomized phase II study of azacitidine with or without the PD-L1 inhibitor durvalumab showed no difference in activity between the two arms [44].…”
Section: Key Pointsmentioning
confidence: 99%